Asuhan Keperawatan pada Ny. S dengan Post Operasi Laparatomi Indikasi Hiperplasia Endometrium Atipik di Ruang Nusa Indah RSUD Dr . Soeselo Kabupaten Tegal - Anggun Juniana; Tati Karyawati; Siti Fatimah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Atypical endometrial hyperplasia which is an endometrial charismatic lesion triggered by estrogen in endometrial tissue with a relative deficiency of the imbalanced effect of progesterone deviation (Hum reprod, 2019). The purpose of this paper is to find out and provide nursing care to Mrs. S with post-laparotomy surgery indications of atypical endometrial hyperplasia in the Nusa Indah room of Dr. Soeselo Hospital, Tegal Regency. The method used is a descriptive method and data collection method. From the case review, it was found that the client's main complaint was post-operative abdominal pain. There are two nursing diagnoses found, namely acute pain and risk of infection. Interventions are arranged based on the theory of SDKI, SLKI, and SIKI as well as on the client's condition and can be implemented.